Whispering gallery resonator based on index profiling - Luan, Feng (2013)
A novel whispering gallery mode (WGM) resonator that relies on index profiling instead of shape variation to confine light is proposed and theoretically studied. Analytical derivations show that a parabolic index profile along the resonator axial direction is able to confine light within its two caustics. This enables efficient coupling of WGM by applying evanescent couplers at the caustics.